Fire triggers reestablishment of invasive grasses in a neotropical savanna under restoration - Giles, André L.; Silva, Mateus C.; Mazzochini, Guilherme G.; Flores, Bernardo M.; Rowland, Lucy; Britto Costa, Patrícia; Cure, Marcio B.; Monge, Marcelo; Schmidt, Isabel B.; Abrahão, Anna; Sampaio, Alexandre B.; Almeira Côrtes, Claudomiro; et al. (Restoration ecology, 2025)
Excluding invasive grasses is a significant challenge for neotropical savanna restoration. Invasive grasses alter fire regimes with feedbacks on soil nutrient pools, favoring their own dominance over native species. Here we combine remote sensing with an opportunistic experiment to monitor a savanna under restoration before and after a large natural fire. We measured vegetation and soil fertility in a 4‐year‐old restoration area in Central Brazil, which was subsequently hit by a lightning fire. The restoration area was originally utilized as pasture, dominated by invasive grasses. Over the restoration period, native fast‐growing grasses replaced the invasive species. Within the first year after the fire, we found that the fire had reduced aboveground biomass, species diversity, and abundance of native species with acquisitive resource‐use strategies. Soil phosphorus and pH increased after the fire and favored the re‐invasion of exotic grass species. Our findings suggest that fire occurrence early in the restoration process may trigger exotic grass re‐invasion driven by soil nutrient enrichment. To diminish the re‐invasion risk from exotic grasses in savannas undergoing restoration, managers should beware of the early fire or manage soil fertility after fire events. Successful restoration may also benefit by incorporating native species with high post‐fire recovery capacity.